Roll a Hard Six: Losing Your Noodle in Raymond Federman’s Double or Nothing - Guenther, Shawna (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2015)
Raymond Federman’s Double or Nothing is a convoluted representation of the mentallyunstable mind existing as a series of six characters that are at once separate and conjoined: the horrors and traumatic events of the narrative past dismantle the unified subject into a series of schizophrenic sub-personalities, parts of the destabilized Author’s psyche, existing as separate fragments that eventually collide. Further, the imaginary room emerges as the Fifth Person, promising, but failing, to be a central stabilizer of the other fractured selves. Finally, the design of the text echoes the patterns of the traumatized mind, illustrating the inability of a narrative to construct a stable, unified subject and demonstrating the inadequacy of traditional narrative forms. The text, with its obliterations, cropped phrases, and pictorial manifestations, becomes the Sixth Person. However, in the end, the text shows that the past cannot be erased, explained, or reversed; neither can the experimental nature of the novel reach beyond the traumatized, schizoid subject to represent the horrors of the past that caused the Author’s psychotic breach. Federman has rolled a hard six that will repeatedly fragment and unite, just as the traumatic past continues to repeat itself as one that defies representation.